Morality Behind Bars: Regulating Prison Films in Postwar Hollywood - Hain, Milan (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2024)
The article examines the censorship process related to three Hollywood prison film noirs produced after World War II: Brute Force (1947), Caged (1950), and Riot in Cell Block 11 (1954). The author argues that the combination of a prison setting and film noir’s inherent pessimism and brutality presented particularly “censorable” material for the Production Code Administration, not least because of the conflation of violence and sympathy for prisoners as protagonists. At the same time, however, the research shows that during this period the Production Code Administration was unable or unwilling to adhere to its established practices, which led to a loosening of the rules that had been in place previously. All three films thus contributed in varying degrees to breaking on-screen taboos and to a greater inclination towards cinematic realism.